Recurrence after stopping anticoagulants in women with combined oral contraceptive‐associated venous thromboembolism: A systematic review and meta‐analysis. (25th July 2022) - Abdulrehman, Jameel; Elbaz, Carolyne; Aziz, David; Parpia, Sameer; Fazelzad, Rouhi; Eischer, Lisbeth; Rodger, Marc A.; Cannegieter, Suzanne C.; ten Cate‐Hoek, Arina; Nagler, Michael; Schulman, Sam; Rezende, Suely M.; et al.
Summary: The risk of recurrence after discontinuation of anticoagulation for a combined oral contraceptive (COC)‐associated venous thromboembolism (VTE) is unclear. Therefore, we conducted a systematic review and meta‐analysis to estimate the incidence of recurrent VTE among women with COC‐associated VTE, unprovoked VTE and to compare the incidence of recurrent VTE between the two groups. The Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Embase Classic +Embase and Medline ALL to July 2020 and citations from included studies were searched. Randomized controlled trials, prospective cohort studies and meta‐analyses of these study types were selected. The analysis was conducted by random‐effects model. Nineteen studies were identified including 1537 women [5828 person‐years (PY)] with COC‐associated VTE and 1974 women (7798 PY) with unprovoked VTE. Studies were at low risk of bias. The incidence rate of VTE recurrence was 1.22/100 PY [95% confidence interval (CI) 0.92–1.62, I 2 = 6%] in women with COC‐associated VTE, 3.89/100 PY (95% CI 2.93–5.17, I 2 = 74%) in women with unprovoked VTE and the unadjusted incidence rate ratio was 0.34 (95% CI 0.26–0.46, I 2 = 3%). The recurrence risk in women after COC‐associated VTE is low and lower than after an unprovoked VTE.